Connotations of flower words and phrases in English and Vietnamese / Bùi Quang Chung; Supervisor: Assoc.Prof. Dr. Hoang Tuyet Minh - Bùi, Quang Chung
The purpose of this research is to find out the similarities and differences between the connotations of flower words and phrases in English and Vietnamese. It helps learners learn English well and use them in daily communication, especially, in using connotations of flower words and phrases in English and Vietnamese. This research used qualitative and quantitative approaches. The author uses quantitative method for collecting the data of flower names and their connotations. Qualitative method is used to describe connotations of flower words and phrases. In addition, the author also uses contrastive and comparative analysis so as to make an investigation into the similarities and differences between connotations of flower words and phrases in English and Vietnamese in terms of cultural cognition. The data is collected mainly from the Internet and flower connotations in the book “The Complete Language of Flowers: A Definitive and Illustrated History”. The author focus on popular flowers collected on special occasions including 45 flowers in English and 25 flowers in Vietnamese. The data were analyzed based on Nguyen Hoa (2004)’s framework of connotations and explained based on Tran Ngoc Them (1999)’s and Farzad Sharifian (2007)’s theories on culture. The results of the research show that both the English and the Vietnamese use connotations of flower words and phrases on important occasions. However, due to cultural differences, the English tend to use the connotations acknowledged based on the tales, myths and legends more frequently than the Vietnamese, who mainly use the connotations based on metaphor and metonymy of color meanings formed according to Yin and yang theory, or Feng Shui. This study also suggests some implications for better using connotations of flower words and phrases in English and Vietnamese.